2023
DOI: 10.3390/ijms24021316
|View full text |Cite
|
Sign up to set email alerts
|

Phenylsulfonimide PPARα Antagonists Enhance Nrf2 Activation and Promote Oxidative Stress-Induced Apoptosis/Pyroptosis in MCF7 Breast Cancer Cells

Abstract: The NF-E2-related factor 2 transcription factor (Nrf2) orchestrates the basal and stress-inducible activation of a vast array of antioxidant genes. A high amount of reactive oxygen species (ROS) promotes carcinogenesis in cells with defective redox-sensitive signaling factors such as Nrf2. In breast cancer (BC), emerging evidence indicates that increased Nrf2 activity enhances cell metastatic potential. An interconnection between peroxisome proliferator-activated receptors (PPARs) and Nrf2 pathways in cancer h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…PPAR encompasses three isoforms: PPARa, PPARb/d, and PPARg-a nuclear receptor family pivotal in regulating and transcribing target genes, energy metabolism, cellular dynamics, inflammation, and carcinogenesis (42,43). The interplay between the PPAR pathway and chemoresistance has garnered attention across diverse cancers, including diffuse large B-cell lymphoma (DLBCL) (44), breast cancer (45), hepatocellular carcinoma (HCC) (46), non-small cell lung cancer (NSCLC) (47), and OC (48). In addition, activation of the PPAR gamma signaling pathway can balance the release of inflammatory and anti-inflammatory cytokines, orchestrating a pre-malignant microenvironment that promotes cell senescence, and alleviating tumor burdens (49).…”
Section: B Amentioning
confidence: 99%
“…PPAR encompasses three isoforms: PPARa, PPARb/d, and PPARg-a nuclear receptor family pivotal in regulating and transcribing target genes, energy metabolism, cellular dynamics, inflammation, and carcinogenesis (42,43). The interplay between the PPAR pathway and chemoresistance has garnered attention across diverse cancers, including diffuse large B-cell lymphoma (DLBCL) (44), breast cancer (45), hepatocellular carcinoma (HCC) (46), non-small cell lung cancer (NSCLC) (47), and OC (48). In addition, activation of the PPAR gamma signaling pathway can balance the release of inflammatory and anti-inflammatory cytokines, orchestrating a pre-malignant microenvironment that promotes cell senescence, and alleviating tumor burdens (49).…”
Section: B Amentioning
confidence: 99%
“…Currently, studies in tumors have indicated that elevated levels of ROS can induce pyroptosis, which is beneficial in combating cancer. For example, the Nrf2/PPARα molecular axis in breast cancer overcomes chemotherapy resistance and leads to better clinical outcomes by promoting pyroptosis ( 98 ). Rongjun Zhang et al.…”
Section: Ros Regulates Pyroptosis In Cancermentioning
confidence: 99%
“…A recent study has shown that such a combination of inhibitors induces alterations in the tumor immune microenvironment associated with an increased cancer cell death via pyroptosis [ 103 ]. In this line, newly synthetized phenylsulfonimide PPAR⍺ antagonists induced apoptosis and pyroptosis of MCF7 breast cancer cells via Nrf2 activation and promotion of oxidative stress [ 104 ].…”
Section: Gasdermins Pyroptosis and Cancermentioning
confidence: 99%